Comparison of Reduced-Length FFT-Based Feature for Induction Motor Fault Classification - Taweewat, Pat; Suwan-Ngam, Warachart; Songsuwankit, Kanoknuch; Konghuayrob, Poom (My University, 2025)
This research presents a comparison of FFT-based features which can be used for classifying induction motor faults via neural network. In this paper, the misalignment and rotor bar damage faults are investigated by using stator current as input data only. As the length of the full FFT can include both informative data corresponding to the faults and uninformative data such as noise from environment or electrical supply, only relevant magnitude from FFT bins should be selected and used instead. This paper proposed to use threshold level determined from the magnitude of FFT bins in dataset as a criterion for the selection. From experimental results, an input feature vector created by proposed method can create short input feature vector length to be used by neural network efficiently. The trained neural network performs classification task at 99.98% in accuracy. Comparing to using dimension reduction by PCA, thresholding method needs basic computation, and yields result close to PCA method.
Keywords: dimension reduction; FFT feature; MCSA; Motor faults; Neural network